The rheological properties of bovine β-Lactoglobulin stabilized oil/water interfaces depend on the protein's quaternary structure. (November 2021) - Ramamirtham, Sashikumar; Whitby, Catherine P.; Zare, Davoud; Weeks, Mike; Williams, Martin A.K.
Abstract: Structural manipulation of β-lactoglobulin through processes such as heat treatment and complexation with other molecules has proven fruitful in industrial formulations. To fully appreciate the ramifications of such methods on protein interfacial adsorption we have investigated assemblies of β-lactoglobulin at oil/water interfaces predominantly at pH 3 and at different conditions of ionic strength, salt type and temperature. These parameters were tuned to vary the relative amounts of two native species, namely, monomer and its smallest aggregate, the dimer, while the interface was monitored using rheology and tensiometry. Unfolding of β-lactoglobulin at the interface triggers the formation of disulfide linkages between the free thiol groups of two monomers which are located at cys121. In this way, monomers pair up to form discrete assemblies of two β-lactoglobulin molecules (non-native dimers) that are not interconnected further and this is reflected in the absence of a viscoelastic layer in solutions with high monomer concentrations. Native dimers however form primary particles capable of forming two thiol bonds allowing the formation of extended networks. A higher concentration of dimers increases the final interfacial elastic strength of the network. This fundamental relation between the quaternary structure of β-lg and its subsequent interfacial network suggests a possible interfacial role in its biological function. Graphical abstract: Image 1 Highlights: Amount of monomer and dimer species of β-lactoglobulin were varied at acidic pHs (3–4) using ion type and ion concentration Interfacial shear elastic strength ( G i ′) of β-lactoglobulin exhibited a correlation with the dimer concentration Monomeric solutions of β-lactoglobulin neither formed an elastic interface nor reduced the surface tension considerably